220 EXPOSURE TO HYPEROXIA CAUSES OXIDATIVE STRESS AND INCREASES APOPTOTIC-LIKE CELL DEATH IN THE MURINE DEVELOPING BRAIN. (1st January 2006) - Handley, S.; Wang, X. P.; Sola, A.; Wen, T. C.; Genetta, T.; Moore, J.; Rogido, M.
Abstract : Background: Exposure to hyperoxia has been associated with significant perinatal morbidity such as retinopathy of prematurity and bronchopulmonary dysplasia but the effect of hyperoxia on the developing brain is less known. Studies have shown that hyperoxia results in apoptosis in the immature murine brain in several animal models. However, little is known about the effect of hyperoxia on neural progenitor/stem cells in the developing brain. Objectives: To determine the effects of exposure to high (FiO2 of 1.0) versus room air oxygen concentrations (FiO2 of 0.21) on the neural progenitor/stem cells in newborn mice. Design/Methods: Five-day-old transgenic mouse pups that express green fluorescent protein (GFP) under control of the nestin gene were randomized into 2 groups. Animals were subjected to either normoxic conditions (FiO2 of 0.21) (n = 4) or hyperoxic conditions (FiO2 of 1.0) (n = 4) for 90 min. Twenty-four hours after the experiment, pups were euthanized and their brains harvested, fixed, and cryosectioned. Apoptotic-like changes were assessed by terminal transferase-mediated dUTP nick end labeling (TUNEL).Oxidative stress was assessed by immunohistochemical methods using a monoclonal antibody against 4-hydroxy-2-nonenal (HNE), a lipid peroxidation product. Positive cells were counted in 20 different fields in 4 different slices per animal, including cortical region and ventricular zone. Results: Neural cells showed weak and patchy HNE immunoreactivity in cortex and ventricular/subventricular zone (VZ) in control pups exposed to.normoxic conditions. Pups exposed to hyperoxic conditions showed marked increase in the intensity of immunoreactivity as well as the number of HNE+ cells, both in cortical (mean 6 SD: 568 6 164 vs 55.3 6 24; p = .0001) and VZ regions (311 6 103 vs 78 6 49; p = .01) On preliminary visual analysis the number of TUNEL+ cells appears to be higher after exposure to hyperoxia, with a five-fold increase compared to the normoxic pups. Furthermore, the number of nestin+ cells undergoing apoptotic-like changes also appears to be greater in the hyperoxia-exposed pups compared to the control group pups. Conclusions: These preliminary results suggest that exposure to high oxygen concentration causes an increase in oxidative stress markers. High oxygen concentration exposure also appears to increase apoptosis in nestin+ cells, indicating the possible injurious effects of hyperoxia on neural progenitor/stem cells. We are continuing to investigate the behavior of neural stem cells exposed to hyperoxia in the developing brain.